2023
DOI: 10.1093/jsxmed/qdad051
|View full text |Cite
|
Sign up to set email alerts
|

Statins synergize with phosphodiesterase type 5 inhibitors but not with selective estrogen receptor modulators to prevent myofibroblast transformation in an in vitro model of Peyronie’s disease

Abstract: Background Peyronie’s disease (PD) is a fibrotic disorder characterized by plaque formation in the tunica albuginea (TA) of the penis, and we have previously shown that inhibition of transformation of TA-derived fibroblasts to myofibroblasts using a combination phosphodiesterase type 5 (PDE5) inhibitors and selective estrogen receptor modulators (SERMs) is effective in slowing the progression of early PD. Aim The study sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The results showed that simvastatin, PDE5 inhibitors, and SERMs all demonstrated a concentration-dependent decrease in myo broblast transformation. Simvastatin inhibited myo broblast transformation in a synergistic fashion when combined with vardena l [21].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that simvastatin, PDE5 inhibitors, and SERMs all demonstrated a concentration-dependent decrease in myo broblast transformation. Simvastatin inhibited myo broblast transformation in a synergistic fashion when combined with vardena l [21].…”
Section: Discussionmentioning
confidence: 97%
“…Further drug combinations may be of value. As an example, Ilg et al investigated the effect of simvastatin in combination with PDE5is (sildena l, vardena l, and tadala l) or Selective Estrogen Receptor Modulators (SERMs) (tamoxifen and raloxifene) on the transformation of broblasts to myo broblasts in a rat model [21]. Statins have previously been suggested to have anti brotic effects in other organs.…”
Section: Discussionmentioning
confidence: 99%